THE INFLUENCE OF WORK MOTIVATION, WORK DISCIPLINE, AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT THE MADIUN CITY LAND OFFICE - Ine Ardita Indriya Mochtar; Ahadiati Rohmatiah; Mutmainah Mutmainah (Journal of Applied Economics in Developing Countries, 2021)
This study aims to know influence of work motivation, work discipline, and work environment on the performance of the employees of the Madiun City Land Office. The population in this study were 59 employees of the Madiun City Land Office. The sample of this research was 59 people. Sampling using saturated sampling technique. The data analysis technique used the Partial Least Square (PLS) approach and was assisted by the SmartPLS 3.2 software. Data analysis techniques include testing the outer model (measurement model) consisting of convergent validity, discriminant validity, composite reliability, inner model testing (structural model) consisting of variant analysis (R2) or Determination Test, t test, and F test. The results of the study are: 1) work motivation variable (X1) and work environment (X3) partially affect the performance of the Madiun City Land Office employees, 2) work discipline variable (X2) partially has no effect on the employee performance of Madiun City Land Office, 3) work motivation variable (X1), work discipline (X2) and work environment (X3) simultaneously affect the performance of the Madiun City Land Office employees, 4) work environment variable (X3) has the most dominant influence on the performance of the Madiun City Land Office employees. Keywords: Work Motivation, Work Discipline, Work Environment, Employee Performance.